Transcriptional responses of invasive and indigenous whiteflies to different host plants reveal their disparate capacity of adaptation - Xu, Hong-Xing (Sci Rep, 2015)
The whitefly Bemisia tabaci contains more than 35 cryptic species. The higher adaptability of Middle East-Asia Minor 1 (MEAM1) cryptic species has been recognized as one important factor for its invasion and displacement of other indigenous species worldwide. Here we compared the performance of the invasive MEAM1 and the indigenous Asia II 3 whitefly species following host plant transfer from a suitable host (cotton) to an unsuitable host (tobacco) and analyzed their transcriptional responses. After transfer to tobacco for 24 h, MEAM1 performed much better than Asia II 3. Transcriptional analysis showed that the patterns of gene regulation were very different with most of the genes up-regulated in MEAM1 but down-regulated in Asia II 3. Whereas carbohydrate and energy metabolisms were repressed in Asia II 3, the gene expression and protein metabolisms were activated in MEAM1. Compared to the constitutive high expression of detoxification genes in MEAM1, most of the detoxification genes were down-regulated in Asia II 3. Enzymatic activities of P450, GST and esterase further verified that the detoxification of MEAM1 was much higher than that of Asia II 3. These results reveal obvious differences in responses of MEAM1 and Asia II 3 to host transfer.